Inherited disorders of photoprotection: from the clinic to gene therapy. - Taïeb, A.; de Verneuil, H. (European Journal of Pediatric Dermatology, 2008)
The Authors review the physiological bases of the inherited disorders of photoprotection, underlining the relationship between the enzymes involved in melanogenesis and the genes of oculocutaneous albinism. They also linge over the study of the antioxidant mechanisms and particularly over the role of catalase, underlining that indirect gene therapy with antioxidant enzymes could limit photosensitivity of xeroderma pigmentosum and probably of other disorders due to altered photosensitivity.